'Skin Portraiture' in the Age of Bio Art: Bodily Boundaries, Technology and Difference in Contemporary Visual Culture. (June 2018) - Kellett, Heidi
In this article, I consider 'skin portraiture': a mode of representation that privileges quasi-anonymous, fragmented, magnified and anatomized images of skin. I argue that this mode of representation permits a heightened awareness of embodied experiences such as reflexivity, empathy and relationality. Expanding understandings of difference through its engagement with haptic imagery and visuality, skin portraiture reorients the boundaries between 'I'/'not I' and subject/object – often through touch – and challenges the cultural commitment to traditional notions of bodily autonomy. By doing so, skin portraiture functions as an antagonistic form of portraiture; that is, as a kind of anti-portraiture that pushes the genre into an expanded visual field and, at times, beyond representation. Exploring the skin-as-technology metaphor, I show that bio art skin portraiture creates chimeric skins through tissue culturing practices, permitting bodies to become radically relational. Bio art skin portraits celebrate the genetic and cellular differences between bodies through a visible collapse of epidermal boundaries, which engenders a hyper-haptic mode of seeing beyond the subject and her or his skin. Analysing the bio art of Jalia Essaïdi, ORLAN and Julia Reodica, and drawing on the work of Laura Marks and Erin Manning, this article explores the skin-as-technology metaphor in order to offer the arts and humanities an innovative understanding of contemporary embodiment.